Factors affecting runoff and soil erosion: plot-level soil loss monitoring for assessing sustainability of forest management - Hartanto, H.; Prabhu, Ravi; Widayat, A.S.E.; Asdak, C. (2003)
The assessment on key ecological factors affecting runoff and soil erosion and the usefulness of plot-level monitoring of soil erosion was conducted by collecting runoff and soil loss records from 14 runoff plots. The runoff plots were set up in two catchments in Central Kalimantan, Indonesia, where conventional logging and Reduced Impact Logging (RIL) took place. Runoff plots were set up in forest areas with different levels of logging disturbances, i.e. harvesting areas, skid trails and undisturbed/control areas. The magnitude of runoff and soil loss from skid trail plots were found to be the highest, followed by control plots and harvest plots. Canopy cover, sapling density, litter depth and woody debris appeared to be important ecological factors that determine the magnitude of soil loss. The roles of these ecological factors were less significant compared to rainfall in determining the magnitude of runoff. Canopy cover, sapling density, litter depth and woody debris can be measured quantitatively or qualitatively without complicated equipment and methods. Furthermore, they are sensitive to logging disturbance which make them suitable verifiers of soil erosion. Monitoring of soil loss using runoff plots was cost-effective and allowed more direct linkages to be made between management practices and their impacts on runoff and soil erosion so that forest managers can identify problems and take appropriate preventive measures to improve their management practices.